The effect of Peyton’s four-step method for teaching point-of-care ultrasound psychomotor skills: an experimental study - Breunig, Michael; Kingsley, Ryan; Schroeder, Darrell; Kraus, Jason; Plooster, Corbin; Galush, Tiffany; Boldenow, Laura; Ragaisis, Taryn; Regan, Hannah; Schouten, Will M.; Shafay, Raheel; Issa, Meltiady; et al. (The Ultrasound Journal, 2025)
Background: Medical education commonly utilizes the “see one, do one” two-step approach for teaching psychomotor skills; however, recent evidence suggests that Peyton’s four-step method leads to superior learning. There is limited evidence, and almost no high-quality studies, specifically evaluating the effect of Peyton’s Four‑Step method on long-term retention of ultrasound/POCUS procedural skills. The purpose of this research project was to evaluate the effectiveness of Peyton’s four-step method on teaching the POCUS psychomotor skills of image acquisition to novice learners. Additionally, this research project assessed the influence of Peyton’s four-step method at three different points in time during the skill acquisition phase, in the setting of ongoing deliberate skill practice.Methods: A single-blinded, repeated measures interventional study based on experimental design was completed. Physician Assistant students from one large academic medical center were randomized into a control group (using the two-step method) and intervention group (using Peyton’s four-step method). Students were taught POCUS of the aorta, bladder, heart, lungs, and kidneys. Students’ POCUS skills were assessed during the immediate, intermediate, and delayed learning phases. At each assessment, an organ-specific score and a total score were obtained. Scores were compared using a Wilcoxon rank sum test. An ordinal logistic regression analysis was performed using a generalized linear mixed model with a multinomial distribution and cumulative logit link function to assess the overall effect of Peyton’s four-step method.Results: Students who were taught using Peyton’s method were found to have an increased likelihood of higher total scores compared to those taught using usual instruction (OR = 4.2, p = 0.003). Peyton’s method was found to have increased likelihood of higher scores for cardiac (OR = 2.3, p = 0.032), lung (OR = 2.5, p = 0.034), and kidney (OR = 3.0, p = 0.015). Student performance statistically improved with Peyton’s four-step method during the immediate (p = 0.031) and delayed (p = 0.011) skill acquisition phases, but not in the intermediate phase.Conclusion: Peyton’s four-step method improves overall psychomotor skill acquisition for POCUS. Peyton’s four-step method specifically improved psychomotor skills in the immediate skill acquisition phase and the delayed skill acquisition phase. The benefit of Peyton’s four-step method was more prominent in POCUS applications with higher complexity.